MTHFR functional genetic variation and methotrexate treatment response in rheumatoid arthritis: a meta-analysis. (March 2014) - Morgan, Michael D; Al-Shaarawy, Nashwa; Martin, Steve; Robinson, James I; Twigg, Sarah; , YEAR Consortium; Magdy, Awadalla A; Omar, Aziza Sayed; Ghattas, Maivel H; Emery, Paul; Barrett, Jennifer H; Morgan, Ann W
Aim: To date, functional MTHFR SNPs have been tested for their impact on low-dose methotrexate (MTX) response in small rheumatoid arthritis (RA) cohorts. We sought to test their effect in the single largest cohort studied to date, and undertook a meta-analysis utilizing stringent study inclusion criteria.Materials & methods: RA patients treated with MTX monotherapy from the Yorkshire Early Arthritis Register (YEAR) were genotyped using RFLP assays, and tested for association with treatment efficacy. Studies for meta-analysis were screened by a set of stringent inclusion criteria.Results & conclusion: rs1801131 and rs1801133 were not associated with response to MTX in the YEAR cohort, nor did they affect the probability of achieving a low disease activity state. A meta-analysis of comparable studies found no association with these SNPs. MTHFR SNPs rs1801131 and rs1801133 are unlikely to have a clinically meaningful effect on the first 6 months of MTX treatment in early RA. Original submitted 30 May 2013; Revision submitted 20 November 2013